Strengthening women's economic independence through innovation in Snakehead Fish floss products - Al Hikmah Al Hikmah; Rizka Amalia; Zahiri Marliansyah; Najwa Aliya Safitri; Sulistiani Sepvira; Pamuji Malik (Priviet Social Sciences Journal, 2026)
This study aims to develop the skills and capacity of rural women in processing snakehead fish into high-value dried fish flakes using a Participatory Action Research (PAR) approach involving 24 female participants. Based on the research findings, the diversification of snakehead fish (Channa striata) into dried fish flakes has proven to shift sales patterns from high-risk fresh products to value-added processed products with a longer shelf life. This downstream processing enhances economic stability, reduces the risk of spoilage, and expands distribution reach. The application of hygiene and halal principles further strengthens product quality and market legitimacy. Practical training improved technical skills and production autonomy, while also strengthening the economic role of rural women, and mentoring ensured product quality consistency. Although not yet measured quantitatively, the findings indicate increased value added and reduced dependence on price fluctuations. Thus, this program builds a strong foundation for the sustainable development of household microenterprises.